2022
DOI: 10.1021/acs.jmedchem.1c01792
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-Aminopyrimidine Derivatives as FLT3 Kinase Inhibitors with High Selectivity over c-KIT

Abstract: Herein, we report two promising compounds 30 and 36 possessing nanomolar FLT3 inhibitory activities (IC50 = 1.5–7.2 nM), high selectivity over c-KIT (>1000-fold), and excellent anti-AML activity (MV4-11 IC50 = 0.8–3.2 nM). Furthermore, these two compounds efficiently inhibited the growth of multiple mutant BaF3 cells expressing FLT3-ITD, FLT3-D835V/F, FLT3-F691L, FLT3-ITD-F691L, and FLT3-ITD-D835Y. Oral administration of 30 and 36 at 6 mg/kg/d could significantly suppress tumor growth in the MV4-11 cell-inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Among them, compound A1 was reported as the candidate, which exhibited good kinase inhibitory potency against FLT3, robust antiproliferative activities against MV-4−11 cells and BaF3 cells carrying various FLT3 mutations, suitable oral pharmacokinetic properties, and excellent in vivo antitumor effect. 24 Further kinase profiling indicated that compound A1 also inhibited CHK1, with an IC 50 value of 26.26 nM, indicating the potential to overcome adaptive resistance in FLT3 mutation AML. However, the subsequent patch clamp experiments related to cardiac potassium channels indicated A1 suffered from activity at the hERG ion channel with an inhibition rate (IR) of 75% at the concentration of 20 μM (Figure 1), predicting potential electrocardiogram (QT) prolongation risk, which blocks its further progression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, compound A1 was reported as the candidate, which exhibited good kinase inhibitory potency against FLT3, robust antiproliferative activities against MV-4−11 cells and BaF3 cells carrying various FLT3 mutations, suitable oral pharmacokinetic properties, and excellent in vivo antitumor effect. 24 Further kinase profiling indicated that compound A1 also inhibited CHK1, with an IC 50 value of 26.26 nM, indicating the potential to overcome adaptive resistance in FLT3 mutation AML. However, the subsequent patch clamp experiments related to cardiac potassium channels indicated A1 suffered from activity at the hERG ion channel with an inhibition rate (IR) of 75% at the concentration of 20 μM (Figure 1), predicting potential electrocardiogram (QT) prolongation risk, which blocks its further progression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Changing the position of the N atom in the 1,2,3,4-tetrahydroisoquinoline moiety of Our previous research has demonstrated basis fragments at the ribose or solvent region were crucial for maintaining excellent FLT3 and CHK1 kinase potencies. 24,33 Based on compound 18, we further investigated the effects of various R 1 groups against FLT3-D385Y and CHK1 kinases while keeping B--COR 3 same as in 18. Compounds 29−49 were synthesized and evaluated for their kinase inhibitory activities against FLT3-D835Y, CHK1 and antiproliferative activities against MV-4−11 cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the same line of reasoning, 2-aminopyrimidine derivatives were synthesized with the aim of selectively inhibiting FLT3 -ITD and its mutant forms while sparing the c-KIT kinase, thus reducing the myelosuppressive effect [ 66 ]. Compounds 30 and 36 inhibited the growth of MV4-11 cells and of Ba/F3 cells engineered to express FLT3-ITD, FLT3 D835V/F , FLT3 F691L , FLT3-ITD F691L and FLT3-ITD D835Y .…”
Section: Novel Molecules Targeting Proliferative Mechanisms In Acute ...mentioning
confidence: 99%
“…Substituted isoquinolinones and naphthyridinones form an important class of compounds in the pharmaceutical industry. , Particularly, substituted isoquinolin-1­(2 H )-one, which constitutes the core scaffold of marketed or reported small molecular inhibitors, such as Duvelisib, compound 4 , and Eganelisib, made this heterocycle a popular pharmacophore for synthetic chemists (Scheme , compounds 1 , 3 , and 4 ). Naphthyridinone also acted as a small molecular inhibitor against some medicinal targets (compounds 2 , 5 , 6 ). The Ullmann coupling reaction or multistep cyclization are commonly used to construct N -phenyl-isoquinolinone segments. , However, these suffer from several limitations, such as expensive copper salts, air-sensitive ligands, and harsh reaction conditions, thus hampering the application of conventional synthetic methods…”
Section: Introductionmentioning
confidence: 99%